Urinary Markers of Tubular Injury in HIV-Infected Patients - Temesgen Fiseha; Angesom Gebreweld (Biochemistry Research International)
Renal disease is a common complication of HIV-infected patients, associated with increased risk of cardiovascular events, progression to AIDS, AIDS-defining illness, and mortality. Early and accurate identification of renal disease is therefore crucial to improve patient outcomes. The use of serum creatinine, along with proteinuria, to detect renal involvement is essentially to screen for markers of glomerular disease and may not be effective in detecting earlier stages of renal injury. Therefore, more sensitive and specific markers are needed in order to early identify HIV-infected patients at risk of renal disease. This review article summarizes some new and important urinary markers of tubular injury in HIV-infected patients and their clinical usefulness in the renal safety follow-up of TDF-treated patients.